Разработка мощных вентильно-индукторных электроприводов для шаровых мельниц - Остриров, Вадим Николаевич; Козаченко, Владимир Филиппович; Трофимов, Сергей Александрович; Дмитриев, Вячеслав Юрьевич (НТУ "ХПИ", 2013)
The report examines the development of high-power switched reluctance drives for grinding mills. The usage of sectioned power converter and multi-packet motor design ensures manufacturability and scalability when using the classi-cal algorithm of autoswitching phase, and eliminate the need for a loading machine for the motor testing.
Development of high-power switched reluctance drives for ball mills
Keywords: интеллектуальный комплектный электропривод; вентильно-индукторные двигатели; автоидентификация параметров; автонастройка; регулятор скорости; приемо-сдаточные испытания